Relationship Between Family Support and Adherence to Antiretroviral Medication in Patients with HIV at Bhayangkara Hospital, Indramayu, Indonesia - Carsita, Wenny Nugrahati; Rusyani, Julisah; Windiramadhan, Alvian Pristy Windiramadhan; Prabowo, Ridho Kunto Prabowo (Babali Publisher, 2025)
Introduction: Adherence to antiretroviral (ARV) treatment is one of the most critical factors in the successful management of HIV patients. Family support significantly influences treatment adherence, as family members are closest to the patient and are expected to provide motivation and monitor adherence to ARVs. This study aimed to determine the relationship between family support and ARV adherence among HIV patients. Methods: This study employed an analytic design with a cross-sectional approach. The population comprised HIV patients undergoing treatment in the Treatment Support Care Room (PDP) at Bhayangkara Indramayu Hospital, with an average monthly visit rate of 375 patients. A sample of 190 respondents was selected using the Z formula. The sampling technique employed purposive sampling based on inclusion and exclusion criteria. Bivariate analysis was performed using the chi-square test. Results: The findings revealed that 97 respondents (51.1%) reported good family support, and 146 respondents (76.8%) were compliant with taking ARV medication. The statistical analysis showed a p-value of 0.006 (α < 0.05). Conclusion: There is a relationship between family support and adherence to ARV medication in HIV patients. It is recommended for nurses to educate families to provide support to HIV patients in ARV treatment.